Nilai-Nilai Pendidikan Karakter Novel Menak Jinggo Sekar Kedaton Karya LKH dan Relevansinya dengan Pembelajaran Sastra di SMA - Ayu Linda Wulandari (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2017)
Menak Jinggo Sekar Kedaton novel by Langit Kresna Hariadi (LKH) Describe and explain socio-cultural of society in Majapahit Kingdom. Thenovelusesstudy ofsociology literaturereviews. The purpose of this research are to explain sociology aspects that revealed in Menak Jinggo Sekar Kedaton novel by LKH, the sociology of that situation on the novel, cultural value on the novel, the readers’ response to the Menak Jinggo Sekar Kedaton novel about the character education value and the relevance in learning of literature in senior high school. This research design was used descriptive qualitative. The data resource in this research is Menak Jinggo Sekar Kedaton novel by LKH. The technique that was used purposive sampling. The data analysis technique was interactive model analysis. The validity of thedata usestriangulationof resource,method, researcher, andtheory. The data analysis techniques were reduction of data, presentation of data, and conclusions. Research results could be concluded that the social aspect of the Majapahit culture revealed in the novel of which religious system, society systems, systems of knowledge, language systems, systems of art, livelihood systems, and equipment life systems. Based on the responses of readers in the area of Banyuwangi and Surakarta, the novel gives a positive contribution and contains values character education that have relevance to the study of literature in senior high school.